Comparison of the Effects of a Genetic, a Mild Encephalitis, and a Psychosocial Causal Explanation of Schizophrenia on Stigmatizing Attitudes – a Pilot Study With a Quasi-Experimental Design - Haouchet, Sonja; Harder, Carolin; Müller, Sabine (Frontiers in Psychiatry, 2021)
Background: Previous research has shown that the endorsement of biogenetic causal explanations of schizophrenia is associated with stronger stigmatizing attitudes against people with schizophrenia than the endorsement of psychosocial explanations. However, little is known about whether different biogenetic causal explanation beliefs differentially affect stigmatizing attitudes. Particularly, it is unknown how the endorsement of the mild encephalitis hypothesis of schizophrenia affects stigmatizing attitudes. Aim: The purpose of this pilot study was to examine to what extent different causal explanations of schizophrenia (genetic explanation, mild encephalitis hypothesis explanation, and psychosocial explanation) influence the desire for social distance from persons with schizophrenia. Methods: A study with a prospective, quasi-experimental design was carried out with students in Germany (N = 333). A case vignette depicting a person with typical symptoms suggestive of schizophrenia was presented, and a social distance scale (SDS) was used to measure the stigmatizing attitude against the person described. The participants were randomly assigned to one of three groups receiving different causal explanations of schizophrenia (genetic, mild encephalitis hypothesis, or psychosocial). Results: A one-way ANOVA showed that the mean SDS was lowest in the group with the mild encephalitis hypothesis explanation, followed by the genetic explanation group, and highest in the psychosocial explanation group. However, the differences between the groups were small and not significant. A subanalysis revealed a significant interaction between gender and causal explanation. Women showed a significantly lower desire for social distance than men when receiving the mild encephalitis hypothesis as a causal explanation. Neither the study discipline nor the number of semesters of study had significant effects on the mean SDS. Conclusion: The present study fits into the overall picture of previous research, which has found that biogenetic beliefs were either associated with more social distance or did not yield a statistically significant association. Our hypothesis that endorsement of the mild encephalitis hypothesis would reduce the desire for social distance was confirmed for women, but not for men. However, we do not recommend gender-specific anti-stigmatization campaigns, not only because the effects were small, but because group-specific campaigns can rightly raise suspicions of dishonesty and manipulation.